The Layered Structure of Poly[[Hexaaqua(L4-Benzene-1,2,4,5- Tetracarboxylato) Dicopper(Ii)] Tetrahydrate] - Venegas-Yazigi, D; Venegas-Yazigi, D (2013)
In the structure of the title compound, {[Cu2(C 10H2O8)(H2O)6] ·4H2O}n , the benzene-1,2,4,5-tetracarboxylate ligand, (btec)4-, is located on a crystallographic inversion centre in a ?4-coordination mode. The coordination environment of each pentacoordinated CuII centre is square pyramidal (SBP), formed by three water molecules and two carboxylate O atoms from two different (btec) 4- ligands. The completely deprotonated (btec)4- ligand coordinates in a monodentate mode to four CuII atoms. The alternation of (btec)4- ligands and SBP CuII centres leads to the formation of a planar two-dimensional covalent network of parallelograms, parallel to the ab plane. Hydrogen bonds between a basal water molecule and an apical one from an adjacent [Cu(btec)0.5(H2O)3] unit exist in the intralayer space. Hydrogen bonds are also present between the two-dimensional network and the water molecules filling the channels in the structure. © 2013 International Union of Crystallography.